ACUTE EXACERBATIONS ON CHRONIC OSTRUCTIVE PULMONARY DISEASE (COPD) WITH SECONDARY INFECTION - Nanang Hidayatulloh (Fakultas Kedokteran Universitas Lampung, 2015)
Chronic obstructive pulmonary disease (COPD) is a disease that can be prevented and treated. This disease cause some significant extrapulmonary symptoms which can result in different levels of severity for each individual. The main cause of COPD is cigarette, the smoke pollution from burning, and harmful gas particles. Acute exacerbations on COPD is associated with secondary infection in respiratory tract. Male, 77 years old, came with complaint of shortness of breath since 4 days before hospitali admission. Shortness arise when patient on activity and reduce while resting. Patient also complained of cough with greenish-yellow sputum since 3 years ago. On physical examination found barrel chest, vocal fremitus weakened, hipersonor percussion, and wheezingauscultation in both lung fields. Laboratory tests showed leukocytosis (11,000/ul), spirometry VEP1 45%, and x-rays looked impression of COPD. Patients was given supportive therapy with oxygen 2 liters/minute, pharmacological therapy of salbutamol + ipratropium bromide nebulizer every 8 hours, dexametasone injection of 5 mg every 8 hours, daily antibiotic ceftriaxone 2 grams, and mucolytics continued with medical rehabilitation. [J Agromed Unila 2015; 2(1):57-62]Keywords: chronic obstructive pulmonary disease, cigarette, cough, male, shortness of breath